Continence promotion in health education and community outreach programmes - Myra Robson; Amarachi Olu (British Journal of Community Nursing, 2026)
Incontinence is a highly stigmatised condition that can significantly impact an individual's quality of life, yet few people seek proper assessment and treatment. Therefore, outreach events aimed at specific or general patient groups can play a crucial role in creating awareness of the condition. This article discusses some of the principles behind health promotion and outreach activities, and the importance of health literacy. It suggests some questions to consider when planning outreach activities and ideas of possible events. Two case studies from the authors’ community service have been included as examples.